Adherence with direct oral anticoagulants in patients with atrial fibrillation: Trends, risk factors, and outcomes. Issue 1 (18th November 2021) - Arbel, Anat; Abu‐Ful, Zomoroda; Preis, Meir; Cohen, Shai; Saliba, Walid
Abstract: Background: Adherence to direct oral anticoagulants (DOACs) remains a concern among non‐valvular atrial fibrillation (AF) patients. We aimed to assess patterns of adherence with DOACs and examine their association with ischemic stroke and systemic embolism (SE). Methods: This retrospective cohort study includes all adult members of Clalit Health Services, the largest healthcare provider in Israel, with newly diagnosed non‐valvular AF between January 2014 and March 2019, who initiated DOACs within 90 days of AF diagnosis and used DOACs exclusively. Adherence was assessed using the proportion of days covered (PDC) over the first year of treatment, and high adherence was defined as PDC ≥80%. Regression models were used to identify predictors of high adherence to DOACs and to examine the association between adherence and stroke or SE. Results: Overall 15, 255 patients were included in this study. The proportion of highly adherent (PDC ≥80%) DOACs users was around 75% and decreased slightly over the years. On multivariable analyses, the likelihood of high adherence to DOACs increased with age and across higher socioeconomic classes, and was more likely among females, Jews, statins users, and patients with CHA2 DS2 ‐VASc score ≥2. Risk of stroke and SE was lower among highly adherent DOACs users; adjusted HR 0.56 (95% CI, 0.45–0.71), compared to users with PDC <80%. Conclusions: Adherence with DOACs is still sub‐optimal among non‐valvular AF patients, resulting in a higher risk of stroke and SE. Abstract : High adherence to DOACs reduces the risk of stroke and systemic thromboembolism. With approximately 75% of patients highly adhering to DOACs, adherence is suboptimal. Older age, higher socioeconomic class, female sex, Jewish ethnicity, and CHA2DS2‐VASc score≥2 are predictors of high adherence.